2015
DOI: 10.1186/s12891-015-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and acquired organ damage are intimately related to activity limitations in patients with systemic lupus erythematosus

Abstract: BackgroundSystemic lupus erythematosus (SLE) is an autoimmune multi-organ disease, characterized by episodes of disease flares and remissions over time, which may restrain affected patients’ ability to perform daily activities. The purpose of the present study was to characterize variation in activity limitations among well-defined SLE patients, and to describe disease phenotypes, acquired organ damage and their relations to activity limitation and self-reported health, respectively.MethodsThe disease phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 47 publications
3
43
1
Order By: Relevance
“…Function as measured by mHAQ was influenced strongly by disease activity, but not by damage. Other studies showed a correlation of HAQ (Health Assessment Questionnaire) with both SLEDAI and SDI [31, 32]. In our study a relationship between health statuses measured by mHAQ was not significantly correlated to damage, possibly due to the limited size of our cohort and also since mHAQ was used, as opposed to HAQ.…”
Section: Resultscontrasting
confidence: 72%
“…Function as measured by mHAQ was influenced strongly by disease activity, but not by damage. Other studies showed a correlation of HAQ (Health Assessment Questionnaire) with both SLEDAI and SDI [31, 32]. In our study a relationship between health statuses measured by mHAQ was not significantly correlated to damage, possibly due to the limited size of our cohort and also since mHAQ was used, as opposed to HAQ.…”
Section: Resultscontrasting
confidence: 72%
“…In summary, SOC worked, but did not lead to remission in all patients. As expected from personal contact and from the literature [ 9 , 10 ], the majority of patients reported problems with paid work, social life and leisure activities including traveling (Fig. 2 ).…”
Section: Resultssupporting
confidence: 72%
“…SLE is a complex autoimmune multisystemic disease, with a huge impact on quality of life and development of organ damage [ 34 , 35 ]. Despite having a large number of studies clarify many aspects of the pathogenesis of this disease, a comprehensive understanding of the immunological phenomena underlying the clinical manifestations of SLE still remains a challenge [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%